THE PARTICIPATION AND UTILIZATION OF NATIONAL HEALTH INSURANCE (JKN) AMONG INDIGENOUS PAPUAN PEOPLE (OAP) IN JAYAPURA DISTRICT, PAPUA PROVINCE - zamuli, habibi (Insights in Public Health Journal, 2025)
The article 28H of the 1945 Constitution of the Republic of Indonesia stipulates that health is a fundamental human right and a key element of national welfare that must be realized in accordance with the ideals of the Indonesian nation, without exception. At present, the National Health Insurance (JKN) coverage in Papua Province has reached approximately 1.3 million individuals out of a total population of 1.5 million. The JKN participation rate among the indigenous Papuan population (Orang Asli Papua, OAP) in Jayapura Regency is recorded at 76%, comprising 50% OAP originating from outside Jayapura Regency and 20–25% representing local clans within Jayapura Regency. This study employed a descriptive quantitative research design, involving a sample of 531 respondents selected through simple random sampling. The findings reveal that 87.94% of the OAP community possesses JKN membership. The types of health insurance held by OAP respondents are distributed as follows: 78.53% under JKN, 6.59% under the Papua Health Card (Kartu Papua Sehat, KPS), and 14.87% under other schemes such as Regional Health Insurance (Jamkesda) and Maternity Insurance (Jampersal). Furthermore, 53.11% of OAP respondents reported having been JKN members for one year or less. With regard to service utilization, 43.12% of respondents expressed dissatisfaction with the quality of healthcare services received, whereas 74.95% indicated that the administrative process for obtaining JKN membership was straightforward. In terms of perceived fairness, 75.14% of the respondents believed that the distribution of JKN and KPS memberships was equitable. Conclusion: The ownership rate of National Health Insurance (JKN) among the OAP population is relatively high. JKN membership, predominantly through BPJS Kesehatan, constitutes the main form of health insurance ownership, with the majority of participants having enrolled within the past year. Although nearly half of the OAP community reported dissatisfaction with the healthcare services received, the administrative processes associated with JKN enrollment were generally perceived as accessible. Moreover, the majority of respondents considered the distribution of JKN and KPS memberships to have been conducted fairly.